Analisis Yuridis terhadap Kewenangan Pengawas Ketenagakerjaan dalam Perlindungan Korban Kecelakaan Kerja - Rini Marselin Kaesmetan; Limrogate Immanuel (Universitas Medan Area, 2026)
This study aims to analyze the legal framework governing the authority of labour inspectors in providing legal protection for victims of occupational accidents, examine the forms of legal protection available under Indonesian positive law, and identify the normative challenges in the implementation of labour inspection. This research employs a normative legal research method using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary sources collected through library research and analyzed qualitatively using legal interpretation and deductive reasoning. The findings reveal that the authority of labour inspectors is comprehensively regulated under Indonesian legislation, empowering them to conduct supervision, inspection, law enforcement, and investigation of labour law violations. Legal protection for occupational accident victims is implemented through monitoring compliance with occupational safety and health standards, ensuring participation in the national employment social security scheme, and imposing administrative and criminal sanctions for violations committed by employers. However, the effectiveness of these authorities remains constrained by regulatory inconsistencies, limited institutional capacity of labour inspectors, low employer compliance with labour regulations, and weak inter-agency coordination. Therefore, strengthening the legal framework, institutional capacity, and inter-agency collaboration is essential to ensure more effective legal protection for victims of occupational accidents.